(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Covid-19 pandemic has significantly influenced all sectors of economy. Banking sector, being an integral part of financial system, has also been largely influenced by such pandemic. Thus, an attempt is made to assess the performance of banks during the covid pandemic from customer perspective. The study analyses the influence of digital banking and employee behaviour on bank performance. The impact of customer adjustment is also examined. Structural equation modelling is applied for data analysis and hypothesis testing. The study reveals that there is a significant influence of digital banking and employee behaviour on the bank performance. Whereas customer adjustment has no impact on the performance of banks during covid-19 pandemic. The findings of the present study will halp banks to revamp their strategies to improve their performance by neutralizing the pandemic effect.